Factors that affect the adhesion of fixed orthodontic appliances. Literature review - Munive Mendez, Arnaldo Alfredo (2023)
The adhesion of fixed orthodontic appliances and dental enamel is an important procedure, which must be correctly planned with the materials assigned for each clinical situation, which can be variable due to the dental surface, the medical and stomatological history of the patient. In addition, to allow effective treatment in clinical practice, factors affecting cementation must be taken into account, which may be related to clinical materials such as acid etching, bracket type, bracket design and size, adhesive, and adhesion to restorative materials. Also, they may be related to the dental surface, such as fluorosis, a defect in the dental surface that affects the quality of the enamel. On the other hand, there are extrinsic factors such as mouthwashes, smoking or dental whitening. Finally, it is imperative to mention that this literary review was carried out through previous studies, where they evaluated orthodontic adhesion techniques to achieve better clinical management, which allow the success of orthodontic treatment, such as shear bond strength, adhesion index remnant, in vivo survival analysis and microscopic evaluation of the microfracture.